The Influence of the Communication Process on Agro Innovation Park Mentoring Program on the Performance of Bogor Women Farmer Groups - Islami, Mutiara Shima; Sugihardjo; Widayanti, Emi (Jurnal Penyuluhan Pertanian, 2023)
Agro Innovation Park (Tagrinov) is an innovation in the display of technology for the use of yards at BBP2TP which functions as a place for education regarding the optimal arrangement of yard areas. Tagrinov's activity is to provide services for innovative technology mentoring activities for the use of yards. The farmer women's group is one of the communities that have received Tagrinov's mentoring services. This study aims to determine the effect of the communication process in the Agro Innovation Park (Tagrinov) mentoring program on the performance of women's farmer groups in Bogor through the intervention of the communication effect variable. The research method is quantitative. The research location is Bogor City. The sample was determined by proportional random sampling method of 55 respondents. Data analysis used path analysis using the IBM SPSS 25 application. The results showed that the communication process in the Agro Innovation Park mentoring program through communication effects had a significant effect on the performance of women's farmer groups in Bogor.